PSII-8 The effects of supplementing olive pomace on serum and tissue fatty acid composition in spanish goats. (7th December 2018) - Urso, P; Kim, J; Legako, J; Beverly, M; Kelley, S; Anderson, M; Wellmann, K; Johnson, B
Abstract: The objective of this study was to determine if olive pomace could be supplemented at a level that increased the C18:1 concentration in blood and muscle tissue. Mature Spanish-influence goats (n=14; 41.6 kg) were fed ad libitum olive pomace mixed with molasses, starting at 2% of their BW for 28 days. Does were fed in herringbone-style runs daily with BW and blood samples collected biweekly. Biopsies were taken at d 0 and d 28 along the longissimus dorsi. FAs were extracted and measured using FAME and GC-FID, respectively; concentrations of each FA were calculated using C13:0 as an internal standard. All data were analyzed using the GLM and CORR procedure in SAS. There were significant changes in C18:1 and C18:2 in sera over time with mean consumption of 0.55 kg/d over the duration of the trial. From d 0 to d 28, the serum concentration of C18:1 increased (P<0.001) by 8.67% and C18:2 increased (P<0.03) by an average of 4.4%. Serum concentration of C18:0 tended to increase (P<0.08) by 3.6%. There was also no significant increase in C16:0 or C20:4. C18:1 and C18:0 followed a similar pattern of change (r=0.68) with a marked increase in concentration of C18:1 and C18:0 occurring from d 14 to d 28 in sera. This rise in concentration combined with the linear increase of C18:2 in sera may indicate that C18:2 is saturated into C18:1 and then further into C18:0. Within muscle tissue, C18:0 increased by 4.9% and C20:4 increased by 2.3% (P<0.05). Whereas C18:2 tended to increase (P<0.08) by 2.2%. There was also a similar pattern of change observed between C18:2 and C20:4 (r=0.93). Neither C18:1 or C16:0 showed any difference in concentration in the muscle. The olive pomace diet showed to have no effect in increasing monounsaturated fatty acid deposition in muscle tissue.